Restriction of the Use of Certain Hazardous Substances in Electrical and Electronic Equipment Regulations 2012 (as amended) : As they apply to equipment being supplied in or into Northern Ireland from 1 January 2021 : Guidance for economic operators.: As they apply to equipment being supplied in or into Northern Ireland from 1 January 2021 : Guidance for economic operators. (2021) - Unknown
No abstract available